2020
DOI: 10.20473/pmnj.v6i1.17904
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Toddler Toilet Training Readiness in the Kenjeran Community Health Center in Surabaya

Abstract: Introduction: Toilet training for children is an attempt to train children to control bowel movements and urination. Besides, children are encouraged to be able to defecate and urinate in the specified place. The success of toilet training depends on the readiness of the child and family. This study aims to determine the factors that affect toilet training readiness for toddlers.Methods: The research design used is descriptive analysis, with a cross-sectional approach. The population at Kenjeran Community Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…And agree with study conducted in "moradabad district" reported reported that majority of mothers (57%) were having moderate knowledge [10] , [21] . (4) Reveal that no significant levels has recorded at P>0.05 among parent's (SDCv.) and child's (SDCv.)…”
Section: Resultsmentioning
confidence: 96%
“…And agree with study conducted in "moradabad district" reported reported that majority of mothers (57%) were having moderate knowledge [10] , [21] . (4) Reveal that no significant levels has recorded at P>0.05 among parent's (SDCv.) and child's (SDCv.)…”
Section: Resultsmentioning
confidence: 96%
“…dilakukan sejak anak masih di dalam kandungan sampai lima tahun pertama kehidupannya, bertujuan untuk mempertahankan kelangsungan hidupnya serta meningkatkan kualitas hidup anak agar mencapai tumbuh kembang optimal baik fisik, mental, emosional dan sosial serta memiliki intelegensi majemuk sesuai dengan potensi genetiknya. Pertumbuhan dan perkembangan anak secara fisik, mental, sosial, emosional dipengaruhi oleh gizi, kesehatan dan pendidikan (Fatmawati, Arief, & Kurnia, 2020;Pangaribuan, Simanullang, & Poddar, 2020).…”
unclassified